Are Screening Tools for Identifying Human Trafficking Victims in Health Care Settings Validated? A Scoping Review. (July 2022) - Hainaut, Mathilde; Thompson, Katherine J.; Ha, Caryn J.; Herzog, Hayley L.; Roberts, Timothy; Ades, Veronica
Objective: Although many screening tools, resources, and programs for identifying victims of human trafficking exist, consensus is lacking on which tools are most useful, which have been validated, and whether they are effective. The objectives of this study were to determine what tools exist to identify or screen for victims of human trafficking in health care settings and whether these tools have been validated. Method: We conducted a scoping review of the literature on human trafficking identification in health care settings following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) protocol for scoping reviews. We searched the MEDLINE, PsycInfo, Embase, and Scopus databases without language or date limitations. Two independent reviewers screened each citation. We included human research studies in English with populations of all ages, all genders, all geographic locations, and using quantitative and/or qualitative research methods. We excluded studies that were not conducted in a health care setting, review articles, and meta-analyses. We summarized additional screening tools available online and identified through hand-searching. Results: Database searches yielded 8730 studies, of which 4806 remained after removing duplicates. We excluded 4720 articles based on title/abstract review, we reviewed 85 full-text studies for eligibility, and we included 8 articles. Hand-searching revealed 9 additional screening tools not found in the literature. Through our search for validated screening tools, only 6 had been studied for validation in health care settings. Conclusions: Few studies have evaluated screening tools for identifying victims of human trafficking in health care settings. The absence of a gold standard for human trafficking screening and lack of consensus on the definition of human trafficking make screening tool validation difficult. Further research is required for the development of safe, effective approaches to patient screening.